Chinese life in Britain - Šabatková, Ivana (Univerzita Pardubice, 2007)
This bachelor paper is exploring the immigrants experience in a host country. The paper describes and analyzes the process of adaptation of the Chinese ethnic minority in Britain and evaluates the influence of culture, family, and education in the process of integration and assimilation. The essential terminology for this topic is explained at the beginning of the work. The following chapters introduce the period of Chinese arrivals and furthermore deal with the adaptation of the Chinese in the new society and the new life. This work is based on experience of Chinese families, reports of Chinese in Britain and extracts from Timothy Mo's novel Sour Sweet.
Čínský život v Británii
Keywords: migration; immigrants; adaptation; integration; assimilation; nationhood; Migrace; imigranti; adaptace; integrace; asimilace; národní příslušnost; menšiny